The last of August : a Charlotte Holmes novel - Cavallaro, Brittany (Cavallaro, Brittany. Charlotte Holmes novel, 2017)
Jamie Watson and Charlotte Holmes are looking for a winter break reprieve in Sussex after a fall semester that almost got them killed. But nothing about their time off is proving simple, including Holmes and Watson's growing feelings for each other. When Charlotte's beloved Uncle Leander goes missing from the Holmes estate-- after being oddly private about his latest assignment in a German art forgery ring-- the game is afoot once again, and Charlotte throws herself into a search for answers. So begins a dangerous race through the gritty underground scene in Berlin and glittering art houses in Prague, where Holmes and Watson discover that this complicated case might change everything they know about their families, themselves, and each other.